Fashion/Social Advertising. What Happens When Fashion Meets Social Issues - Spalletta, Marica; Ugolini, Lorenzo (Commons. Revista de Comunicación y Ciudadanía Digital, 2016)
<!--[if gte mso 9]> 96 <![endif]--> <!--[if gte mso 9]> Normal 0 14 false false false IT JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria;} --> <!--[endif] --> <!--StartFragment--> “Fashion/social advertising”, as the name suggests, is a composite phenomenon, combining the peculiarities of two specific districts of the advertising empire: “fashion advertising” and “social advertising”. Today, it represents one of the most interesting phenomena in the wide scenario of advertising, because it gives rise to an effective and efficient advertising model in terms of values, texts and practices. However, although social advertising should be grounded on “thinking ethically”, often this “thinking ethically” doesn’t turn into “talking ethically”. This paper aims to understand virtues and vices of the fashion/social phenomenon through two different researches. The first one aims to highlight what is fashion/social advertising and how fashion/social ads talk to the public. The second one focuses on the decisions of Italian Istituto dell’Autodisciplina Pubblicitaria about fashion/social ads, aiming to understand when and how fashion/social advertising doesn’t talk ethically. <!--EndFragment-->